The Use of Conjunction in Students' Writing Recount Text at Second Grade of SMAN 1 Tongkuno - Andani, Melly; Rohmana, Rohmana; Miliha, La (Universitas Halu Oleo, 2019)
This research aims to investigate the types of conjunctions and the accurately use of conjunction in students’ writing. This research was conducted in SMAN 1 Tongkuno. The instrument of this research was students’ writing that focused on recount text. This research employed descriptive qualitative design. The population of this research was the second-grade students of SMAN 1 Tongkuno. The sample of this research is the second-grade students of SMA N 1 Tongkuno consist of 20 students. The researcher collected the data by asking the students to write their personal recount. The technique of data analysis in this study was descriptive analysis, while to analyze the accuracy of conjunction the researcher used criteria of correctness in cohesion that consist of the use of conjunction on students’ writing. The result shows that all of types of conjunction exist in students writing, additive conjunction is the most frequently conjunction used in students’ writing, followed by temporal conjunction, then causal conjunction, and the last adversative conjunction. The accuracy of conjunction used by students on their writing contribute highly because mostly the second-grade students of SMAN 1 Tongkuno use conjunction accurately.